2004
DOI: 10.1158/1055-9965.epi-085-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Glucosinolates to Isothiocyanates after Ingestion of Raw or Microwaved Cabbage by Human Volunteers

Abstract: Cabbage contains the glucosinolate sinigrin, which is hydrolyzed by myrosinase to allyl isothiocyanate. Isothiocyanates are thought to inhibit the development of cancer cells by a number of mechanisms. The effect of cooking cabbage on isothiocyanate production from glucosinolates during and after their ingestion was examined in human subjects. Each of 12 healthy human volunteers consumed three meals, at 48-h intervals, containing either raw cabbage, cooked cabbage, or mustard according to a cross-over design. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
110
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(118 citation statements)
references
References 23 publications
6
110
1
1
Order By: Relevance
“…An important determinant of ITC exposure is the combined influence of cooking and microflora in the intestinal tract: mild-cooking (o75-801C) results in enhanced ITC production by releasing myrosinase, but further cooking prevent further ITC formation, as myrosinase is quickly denaturated when temperature reaches 901C (Dekker et al, 2002). However, ITC may still be formed after eating different types of cruciferous vegetables cooked by different methods (boiled, steamed, microwaved), showing that glucosinolates may be converted to their breakdown products by the myrosinase-like activity of colonic microflora (Getahun and Chung, 1999;Conaway et al, 2000;Rouzaud et al, 2004). However, the hydrolysis of glucosinolates by the microflora appears to be much less efficient than that catalysed by the plant myrosinase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important determinant of ITC exposure is the combined influence of cooking and microflora in the intestinal tract: mild-cooking (o75-801C) results in enhanced ITC production by releasing myrosinase, but further cooking prevent further ITC formation, as myrosinase is quickly denaturated when temperature reaches 901C (Dekker et al, 2002). However, ITC may still be formed after eating different types of cruciferous vegetables cooked by different methods (boiled, steamed, microwaved), showing that glucosinolates may be converted to their breakdown products by the myrosinase-like activity of colonic microflora (Getahun and Chung, 1999;Conaway et al, 2000;Rouzaud et al, 2004). However, the hydrolysis of glucosinolates by the microflora appears to be much less efficient than that catalysed by the plant myrosinase.…”
Section: Discussionmentioning
confidence: 99%
“…Both groups of compounds have been shown to reduce the occurrence of cancer in experimental animals (IARC, 2004), and may have anticarcinogenic effects by several mechanisms (Verhoeven et al, 1997). ITC and indoles are both derived from degradation of glucosinolates by the action of myrosinase, the plant thioglucosidase released after tissue disruption owing to processing, cooking or eating vegetables (Mithen, 2001); myrosinase-like activity has also been demonstrated in the gut microflora, although glucosinolate hydrolysis is much less efficient than the breakdown by the plant myrosinase (Getahun and Chung, 1999;Conaway et al, 2000;Rouzaud et al, 2004). Glucosinolates may be found in several plant families, but Brassicaceae is by far the largest one, and thus the presence of glucosinolates is considered as a distinctive feature of cruciferous vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…with the fact that intake of raw cruciferous vegetables provides two to nine times the amount of isothiocyanates in humans compared with similar intakes of their cooked counterparts (23)(24)(25)(26). Using a cell culture system, we previously showed that dietary isothiocyanates and their urinary metabolites (NAC-ITCs) exerted potent antiproliferative effects on human bladder cancer cells at in vivo -achievable concentrations (4-7).…”
Section: Cancer Epidemiology Biomarkers and Prevention Cancer Epidemiomentioning
confidence: 99%
“…It is noteworthy that the yield of isothiocyanates may be largely reduced by normal cooking procedures due to heat-inactivating myrosinase, destroying heat-labile isothiocyanates and losing glucosinolates (23)(24)(25). Although human intestinal microflora also possess myrosinase activity and is able to partially hydrolyze ingested glucosinolates, studies have shown that isothiocyanate exposure after the consumption of cooked cruciferous vegetables is 60% to 90% less than that after the ingestion of raw cruciferous vegetables (23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation